BIBLIOMETRIC AND CONTENT ANALYSIS: APPLICATION OF THE THEORY OF PLANNED BEHAVIOR IN ENVIRONMENTAL ISSUES - Samputra, Nofi R.A.R; Iskandar, Kurniawaty; Soesilo, Tri Edhi Budhi; Martono, Dwi Nowo (Journal of Environmental Science and Sustainable Development, 2025)
Theory of Planned Behavior (TPB) has been widely applied in environmental science as it closely linked to human behavior. This study aims to analyze research trends, identify potential future research, and propose the development of an integrative TPB model to address gaps in previous research. A total of 120 articles were selected from the Scopus database using rigorous screening criteria, including title-based selection, English-language articles, and a manual abstract review, covering publications up to April 4, 2025. Bibliometrix, VOSviewer, and MindMup were used to support keyword visualization and content interpretation. The results show that China and the United States lead in research contributions, while Africa, despite facing significant sustainability challenges, remains underrepresented. Recent research topics include energy efficiency, climate change, and air quality, which are different from the topics of interest before the COVID-19 pandemic, such as green hotels and tourism. Keyword such as “corporate norm” appear less integrated with other research themes. Further researches are expected to focus more on Africa and incorporate additional behavioral frameworks. In particular, integrating with behavioral models based on altruistic interests (Value-Belief-Norm/VBN), especially for studies in the Asian regions, which have a more dominant collectivist culture than individualism. The weakness of TPB, which only considers cognitive factors, can be addressed by adding affective factors through the Model of Goal-Directed Behavior (MGB). The proposed integration of MGB-VBN-Knowledge holds potential to enhance explanations of public environmental behaviour and formulate more effective policies. The role of corporate norms in shaping environmental behavior also warrants further exploration.